Computer vision, graphics, and image processing : ICVGIP 2016 Satellite Workshops, WCVA, DAR, and MedImage, Guwahati, India, December 19, 2016 Revised selected papers /: ICVGIP 2016 Satellite Workshops, WCVA, DAR, and MedImage, Guwahati, India, December 19, 2016 Revised selected papers. (2017) - Unknown
No abstract available